2002
DOI: 10.1034/j.1399-5618.2002.02229.x
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine in bipolar disorder and cocaine dependence

Abstract: The use of quetiapine was associated with substantial improvement in psychiatric symptoms and cocaine cravings. The findings are promising and suggest larger controlled trials of quetiapine are needed in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(65 citation statements)
references
References 28 publications
5
59
0
1
Order By: Relevance
“…Quetiapine in monotherapy or in combination with the ongoing treatment shows evidence of efficacy for cocaine, amphetamine and methamphetamine use disorder709, 710, 711 (level 3). Risperidone has been studied alone and as an add‐on agent for cocaine and for methamphetamine use disorders with level 3 evidence for efficacy 711, 712…”
Section: Specific Populationsmentioning
confidence: 99%
“…Quetiapine in monotherapy or in combination with the ongoing treatment shows evidence of efficacy for cocaine, amphetamine and methamphetamine use disorder709, 710, 711 (level 3). Risperidone has been studied alone and as an add‐on agent for cocaine and for methamphetamine use disorders with level 3 evidence for efficacy 711, 712…”
Section: Specific Populationsmentioning
confidence: 99%
“…Indeed, quetiapine was associated with substantial improvements in psychiatric symptoms and cocaine craving in a 12-week open-label, add-on treatment trial with 17 outpatients with bipolar disorder and comorbid cocaine dependence [79] , although changes in drug use did not achieve statistical significance. Moreover, a 97.3% reduction of weekly cannabis use has been reported in a group of 8 psychotic patients (4 with schizophrenia and 4 with bipolar disorder) and comorbid cannabis dependence (according to DSM-IV criteria for substance abuse) [80] .…”
Section: Quetiapinementioning
confidence: 96%
“…[26][27][28] The pilot studies of Brown and colleagues [29][30][31] in small numbers of dual-diagnosis patients (n = 17-24) and that of Sattar and colleagues 32 in nine alcoholic patients with nonpsychotic anxiety suggested that quetiapine can reduce alcohol use, anxiety, and cravings for alcohol.…”
Section: Atypical Antipsychotics Quetiapine Previous Datamentioning
confidence: 99%